Design of multi-epitope-based therapeutic vaccine candidates from HBc and HBx proteins of hepatitis B virus using reverse vaccinology and immunoinformatics approaches. - Patricia Gita Naully; Marselina Irasonia Tan; Husna Nugrahapraja; Aluicia Anita Artarini; Reza Aditama; Ernawati Arifin Giri-Rachman (PLoS ONE)
The major problem in cases of chronic hepatitis B (CHB) is the failure of the patient's immune response to eliminate the covalently closed circular DNA (cccDNA) minichromosome of hepatitis B virus (HBV). Epigenetic regulation involving the HBV core protein (HBc) and HBV X protein (HBx) influences the transcription and stability of the cccDNA minichromosome. The HBc and/or HBx-based therapeutic vaccines that have been developed cannot accommodate differences between HBV genotypes. This research aims to design a therapeutic vaccine candidate based on the multi-epitope of HBc and HBx using reverse vaccinology (RV) and immunoinformatics approach. HBc and HBx sequences from 10 HBV genotypes were obtained from the NCBI Entrez Protein database. Epitopes were predicted from consensus sequences, which consisted of 13,610 HBc sequences and 12,333 HBx sequences. The study identified four cytotoxic T lymphocyte epitopes, two helper T lymphocyte epitopes, and five linear B lymphocyte that met the inclusion criteria. The vaccine candidate designed using cholera toxin subunit B and pan HLA DR-binding epitope adjuvants was predicted to be safe, antigenic, stable, and has a global population coverage of 99.43%. Molecular docking and molecular dynamics simulations demonstrated that the vaccine candidate could stably bind to B cell receptor, cytotoxic T cell receptor, and TLR4 for 100 ns. Immune response simulation indicated that it can induce antibody production and the proliferation of B and T cells. It can be concluded that RV and immunoinformatics successfully facilitated the design of a multi-epitope therapeutic vaccine candidate for CHB.